Spatial Control of Carbon Dynamics in Soil by Microbial Decomposer Communities - Pagel, Holger; Kriesche, Björn; Uksa, Marie; Poll, Christian; Kandeler, Ellen; Schmidt, Volker; Streck, Thilo (Frontiers in Environmental Science, 2020)
Trait-based models have improved the understanding and prediction of soil organic matter dynamics in terrestrial ecosystems. Microscopic observations and pore scale models are now increasingly used to quantify and elucidate the effects of soil heterogeneity on microbial processes. Combining both approaches provides a promising way to accurately capture small-scale microbial-physicochemical interactions and to predict overall system behavior. The present study aims to quantify controls on carbon (C) turnover in soil due to the small-scale distribution of microbial decomposer communities in soil. A new spatially explicit trait-based model (SpatC) has been developed that captures the combined dynamics of microbes and soil organic matter (SOM) by taking into account microbial lifehistory traits and SOM accessibility. We performed Monte-Carlo scenario simulations for sets of spatial distributions of microbes that differ in small-scale spatial heterogeneity and microbial community functional composition (oligotrophs, copiotrophs and copiotrophic cheaters). Samples of spatial distributions of microbes were generated using a spatial statistical model based on Log Gaussian Cox Processes which was originally used to analyze distributions of bacterial cells in soil thin sections. Our modelling approach revealed that the spatial distribution of soil microorganisms triggers spatiotemporal patterns of C utilization and microbial succession. Only strong spatial clustering of decomposer communities induces diffusion-limited C availability at the microhabitat scale, resulting in lower aggregated decomposition of C compounds and microbial growth. However, decomposer communities act as functionally redundant microbial guilds with only slight changes in C utilization. The combined statistical and process-based modelling approach bridges microbial biogeography at the microhabitat scale (µm) with emergent macroscopic (cm) microbial and C dynamics. Our study points out the importance of parameterizing functional trait continua of decomposer communities and highlights promising model extensions that may provide further insights into the biological controls on soil organic matter turnover.